Ultrasonography in the diagnosis of asymptomatic hyperuricemia and gout. (1st December 2016) - Puig, J. G.; Beltrán, L. M.; Mejía-Chew, C.; Tevar, D.; Torres, R. J.
ABSTRACT: Sonography has detected urate deposits in 34%–42% of the patients with asymptomatic hyperuricemia. This may prompt reclassification of asymptomatic hyperuricemia into "asymptomatic gout" and consideration of urate lowering therapy (ULT) to resolve urate deposits. In patients with gout and no visible tophi, sonography has detected urate deposits in half of the patients. This may allow diagnosing "tophaceous gout" and influencing the serum urate target level, prophylaxis to avoid acute gout flares during ULT, and clinical follow-up. Current accessibility to sonography may better classify patients with hyperuricemia and gout and contribute to delineate therapeutic objectives and clinical guidance.